Development of a novel convenient Alzheimer's disease assessment scale, the ABC Dementia Scale, using item response theory. Issue 1 (22nd November 2018) - Umeda‐Kameyama, Yumi; Mori, Takahiro; Wada‐Isoe, Kenji; Kikuchi, Takashi; Kojima, Shinsuke; Kagimura, Tatsuo; Ueki, Akinori; Watabe, Toshiyuki; Kudoh, Chiaki; Akishita, Masahiro; Nakamura, Yu; ,
Abstract : Aim: The present study aimed to assess the interrater reliability and construct the validity of a novel, convenient informant‐based Alzheimer's disease assessment scale to prepare its final version. Methods: For the assessment, site investigators, co‐medicals and, if available, medical staff other than doctors or co‐medicals interviewed study informants to assess individuals using this scale. We then analyzed the interrater reliability and construct validity using factor analysis and item response characteristics. Results: In this study, 427 eligible participants were enrolled. We first examined the interrater reliability, and found that the lower limit of the confidence interval of each item was never <0.4 (except for the item "delusion of theft"). After deleting this item, the 14 items of this scale were organized into three domains (activities of daily living, behavioral and psychological symptoms of dementia, and cognitive function) through factor analysis. After discussion of the similarity of two items and their integration into one item, we confirmed that the final version of the 13‐item scale showed almost the same degree of interrater reliability and construct validity as the former version of this scale. Conclusions: The final version of this novel Alzheimer's disease assessment scale had high interrater reliability and construct validity. We named it the ABC (activities of daily living, behavioral and psychological symptoms of dementia, and cognitive function) Dementia Scale. Further studies on its validation are required.Geriatr Gerontol Int 2019; 19: 18–23 .